Modelo Felder-Silverman para el aprendizaje de factorización, en décimo año de educación básica en la unidad educativa ¨Monseñor Leónidas Proaño¨, periodo académico mayo-octubre 2021. - Pérez Chafla, Kleber Wilson (2022)
There are different learning styles, each person has an own way to learn, to assimilate information and retain it; the research outcome is to analyze the different learning styles of “Felder and Silverman model” which is based on the “five dimensions”, in order to explore how “learning styles” influence learning itself. This model was applied in the teaching process of the factorization “curricular block”, in tenth-year basic-education students at Intercultural Bilingual Educational Unit "Monseñor Leónidas Proaño" in May-October 2021 period. The importance of this research topic in the pedagogical process is justified, addressing the different learning styles, and intending to raise the student’s levels of motivation, and achieve better academic performance. The research was developed using a descriptive-level quasi-experimental design. Data collection was performed during synchronous classes in a virtual manner, through two tests in the Google Forms program. Data processing was performed using the IBM-SPSS computer package. The results obtained from statistical data processing clearly show that the students prefer the dimensions where visual learning styles are involved, gathering more interest in the subject. The Sensitive, Verbal, and Sequential learning styles are predominant in the students. Additionally, through testing on the subject, it is shown that “pre-test” the students do not achieve “required learning”; In contrast, after instruction (classes) based in the model to each group, the students are closer to achieve “required learning”, with a clear difference in the experimental group since most of them reach “” required learning” with an average of 7.68, compared to the 6.12 average of the control group. Therefore, it is clearly shown that classes directed towards the different learning styles presented by Felder & Silverman are very useful in the understanding of the subject, since the students obtained a significant improvement in their learning.